PENGARUH MEDIA PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN PENALARAN MATEMATIS SISWA - Dian Sudiantini; Nurjanah Dewi Shinta (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis research is to know the influence of learning media, using Power Point and Conventional, Creative thinking high and low and interaction between the use of learning media and creative thinking to the ability of mathematical reasoning. Method of research used menggunaka experimental method by applying the learning media that is learning media powerpoint, conventional learning media and creative thinking high and low to find out the effect on the ability of mathematical reasoning then conducted a test of mathematical reasoning ability. The subject of research is divided into two groups namely the experimental group and control group as the entire student population SMP Muhammadiyah Cisalak in KecukSukmajaya Depok and a sample of students of class VII A as experimental class and class VII B as kelaskontrol.Penelitian conducted from April to June 2015From the results obtained by the data and then d SPSS analysis with the help of SPSS for the influence of the use of learning media on the ability of mathematical reasoning obtained valueFcount = 22,883> F table = 4.20artinya there are significant influence, for the influence of students' creative thinking to the ability of mathematical reasoning obtained valueFhount = 49,363> F table = 4.20 means there is influence significant, and for pengarang hinteraksi between the use of media learning and creative thinking to the ability of mathematical reasoning obtained valueFhount = 2.704 <F table = 4.20 means there is no significant influence so that no further tests.Keywords: Learning Media, Creative Thinking and Mathematical Reasoning Ability.